How Sense of Place Affects Student Engagement: A Correlational Study in Higher Education Environment - Chit, Yar Zar (Indonesian Journal of Community Services, 2024)
The main aim of this study was to examine how the sense of place impacts the engagement levels of university students. The research employed a correlational design and survey methodology. A sample of 600 university students from three institutions in Meiktila Township, Myanmar, was chosen using a simple random sampling technique. The Sense of Place Revised Scale and Student Engagement Revised Scale were utilized to gauge students' sense of place and engagement. The findings revealed that the sample mean (31.51) exceeded the theoretical mean (27.5) concerning the sense of place, indicating that university students have a robust sense of place in their academic environment. Additionally, all dimensions of the sense of place exhibited a positive correlation with student engagement (r= .532, p< .01). Multiple regression analysis highlighted the sense of place as the most influential predictor of student engagement. The Adjusted R2 result indicated that 28% of student engagement can be elucidated by the sense of place. Consequently, this study underscores the importance of cultivating a satisfactory sense of place for enhancing overall student engagement.